Performing Internet Governance: The Case Study of Youth Participation in The Internet Governance Forum - Daskal, Efrat; Orlova, Anna (AoIR Selected Papers of Internet Research, 2017)
The Internet Governance Forum (IGF) is a multi-stakeholder forum that has convened annually since 2006 to debate issues of internet governance. It is shaped by three kinds of politics: representation, agenda setting, and principles. This study focuses on the politics of representation by analyzing the case study of youth participation in the IGF. Due to financial, political and educational limitations, minority groups, including youth, are often excluded from participating. Since 2006, several institutionalized efforts have been made to get youth involved, though the effectiveness of these efforts is still unclear. To assess these youth related initiatives and to analyze the political processes that enable young people to construct youth representation at the IGF, this study asks, what are the characteristics of youth participation at the IGF? To answer this question, we used several research methods: content analysis of all youth-related materials from IGF meetings (n=35 documents), in-depth interviews with key activists who participated in the IGF (n=5), and participant observations conducted during IGF Mexico in December, 2016. The results are organized according to three themes: (1) the ideal vision of how and why young people should participate in the IGF, (2) the financial and educational difficulties youth in particular encounter when trying to engage in the IGF that diminish their ability to participate, and (3) the future of youth participation in the IGF. Based on these results, we conclude by discussing the socio-political meaning of representation in the IGF.